2024
DOI: 10.1111/jac.12688
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects on ACC deaminase activity in salt‐tolerant plant growth‐promoting rhizobacteria and impacts on rice crop improvement

T. S. Reshma,
C. Dileep

Abstract: The present study focuses on the 1‐aminocyclopropane‐1‐carboxylic acid (ACC) deaminase assay and the rhizospheric interactions affecting enzyme activity. We investigate the efficacy of ACC deaminase‐producing rhizobacterial activity in alleviating salt stress in rice. Among the five selected isolates, only two strains, KFSC2 and PK7, possessed the enzyme activity. The amplification of the acdS gene resulted in gene identification in all five isolates. The newly designed primer in this study was suitable for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Further, it can provide sustainable solutions for improving rice productivity under coastal saline conditions. For instance, very few studies have shown that microbes from the pokkali rice can promote growth and confer tolerance to salt stress in salt-sensitive rice varieties, Fusarium sp., in IR64 rice variety [ 8 ], and Pseudomonas taiwanensis strain PK7 in Uma rice variety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it can provide sustainable solutions for improving rice productivity under coastal saline conditions. For instance, very few studies have shown that microbes from the pokkali rice can promote growth and confer tolerance to salt stress in salt-sensitive rice varieties, Fusarium sp., in IR64 rice variety [ 8 ], and Pseudomonas taiwanensis strain PK7 in Uma rice variety [ 9 ].…”
Section: Introductionmentioning
confidence: 99%